Multi-fidelity parameter tuning of parallel Monte-Carlo tree search variants - Mouton, Alexander (Stellenbosch : Stellenbosch University, 2025)
Mouton, A. 2025. Multi-Fidelity Parameter Tuning of Parallel Monte-Carlo Tree Search Variants. Unpublished masters thesis. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/e4cb5098-5f59-4c10-9f1d-aa69428ba144